2012
DOI: 10.1002/anie.201107747
|View full text |Cite
|
Sign up to set email alerts
|

Formal Alkylation of Allenes through Highly Selective Radical Cyclizations of Allene‐enes

Abstract: Something radical: the first example of alkene-to-allene radical cyclization of allene-enes is reported. The highly chemoselective intermolecular radical addition reaction of the alkene and subsequent, exclusive exo-radical addition to the allene was realized with perfluoroalkyl radicals. A subsequent TBAF-promoted dehydroiodination of the cyclization products forms cyclopentanes and regenerates an allene moiety (TBAF=tetra-n-butylammonium fluoride).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 42 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…In light of these experimental results and previous reports, a possible mechanism was proposed in Scheme . Firstly, iodoperfuloroalkanes can be easily reduced to produce an electrophilic fluoroalkyl radical.…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…In light of these experimental results and previous reports, a possible mechanism was proposed in Scheme . Firstly, iodoperfuloroalkanes can be easily reduced to produce an electrophilic fluoroalkyl radical.…”
Section: Methodssupporting
confidence: 56%
“…To realize the conceptually hydro‐perfluoroalkylation of 1,6‐enynes, our investigation was carried out by employing 1,6‐enyne 1 a as the common substrate with commercially available reagent n ‐C 4 F 9 I (2.0 equiv.) as fluorine source, no product was observed under previous reported similar reaction conditions (Table , entry 1) . Fortunately, when copper catalyst such as CuBr 2 was added, the target product was obtained but only in 12% yield (entry 2).…”
Section: Methodsmentioning
confidence: 73%
“…On the basis of the above experimental results and previously reported mechanisms, a possible mechanism was proposed, as outlined in Scheme . First, the photocatalyst [ fac -Ir­(III)­(ppy) 3 ] is irradiated to the excited state [ fac -Ir­(III)­(ppy) 3 *] under visible light irradiation, which is oxidatively quenched by CF 3 (CF 2 ) 2 CF 2 -I to generate a [ fac -Ir­(IV)­(ppy) 3 ] + complex, a n -C 4 F 9 • radical ( A • ), and an iodine anion.…”
Section: Resultsmentioning
confidence: 72%
“…In the past few years, visible-light photoredox catalysis has been developed as an eco-friendly and highly efficient strategy with the advantages of convenience, availability, and safety. In light of the excellent reductive ability of a photocatalyst in the excited state under mild conditions, photosensitized methods for the generation of perfluorinated radicals from inexpensive and diverse perfluoroalkyl halides are feasible and efficient means for ATRA-type reactions . In general, perfluoroalkyl iodides or bromides were commercially available and much less expensive than other frequently encountered perfluoroalkylating reagents (e.g., Togni’s reagents and R f SO 2 Cl) on a large scale. With our long-standing interest in the difunctionalization of alkenes using perfluoroalkyl halides, we herein demonstrated a visible-light-induced ATRA and cyclization of benzene-tethered 1,7-enynes or N -tethered 1,6-enynes with perfluoroalkyl halides, which realize the concomitant formation of the C-R f and C-X (X = I, Br) bond under mild conditions, leading to 2,4-dihydronquinolin-2­(1 H )-ones and pyrrolidines bearing a wide variety of perfluorinated groups, such as CF 3 , CF 2 Br, C 3 F 7 , C 4 F 9 , C 6 F 13 , C 8 F 17 , C 10 F 21 , CF 2 CO 2 Et, etc (eq 4, Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Typical substrates employed for such tandem reactions include allene- In 2012, the Ma group developed a tandem radical addition/ cyclization reaction of allene-enes. 156 Traditionally, radicals add in a chemoselective fashion to an allene over a competing alkene group, proceeding in an "allene-to-alkene" fashion. 119,157 In contrast, Ma reported that a perfluoroalkyl radical, generated from perfluoroalkyl iodide, chemoselectively attacks the alkene moiety of 393; the subsequent 5-exo-trig cyclization of the resulting alkyl radical occurs at C1 of the proximal allene (Scheme 122) to give vinyl iodides of the form 394, which undergo dehydroiodination with TBAF to form the corresponding allenes 395.…”
Section: Tandem Radical Cyclization Reactionsmentioning
confidence: 99%